Convergence during the oil crisis: A comparison of labour productivity in manufacturing of the planned and market economies - Artem Kochnev (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper examines labour productivity convergence in manufacturing of the planned and market economies in the setting of the oil price shocks of the 1970s. Using the wiiw COMECON Dataset and the KLEMS dataset, the paper constructs a single-digit industry-level productivity metric for selected industries and applies a difference-in-difference estimator to estimate the impact of the oil price shocks on convergence in productivity levels across industries between 1970 and 1985. Although the paper does not find an impact of the oil price shocks on convergence of the command economies, it does detect an accelerating impact on the convergence process of the market economies.
Keywords: O47; N64; P23; L60; Q43; 330; Labor Productivity; Convergence; Planned Economies; Oil price shocks; Manufacturing; Productivity; Competitiveness; Difference-in-Difference; COMECON Dataset; KLEMS Dataset; Structural change